Dinâmica da cobertura vegetal nativa ao longo da bacia hidrográfica do rio Paraíba - Araujo, Lucas Nunes de (2025)
The dynamics of vegetation cover and land use in the various vegetation formations still need to be better understood, as there are multiple causes involved, such as climate variations, the expansion of agriculture and livestock farming, the exploitation of timber products, urban expansion, land structure, cultural and social factors, among others. In Brazil, models that seek to understand variations in vegetation cover and land use focus on the Amazon biome. Our main objective was to investigate how climatic and socioeconomic factors interact with each other and how they interfere with native vegetation cover along the Paraíba River Basin, in the state of Paraíba, between 1995 and 2021. The study area (eight municipalities) is located in the Caatingas and Atlantic Forest Domains and covers the Cariri microregion and the Borborema mesoregion. Sixteen Landsat satellite images and socioeconomic data were obtained. The analysis of vegetation cover in the Cariri Paraibano microregion between 1995 and 2021 revealed that, among the eight municipalities studied, only Livramento presented a strong dependence of vegetation on climate, mainly precipitation. In the other municipalities, land use for agricultural and livestock activities, as well as income distribution, were the main factors that influenced the dynamics of vegetation cover in the Caatinga. These results suggest that the Caatinga vegetation, adapted to drought conditions, is more sensitive to intensive land use practices than to climate variations and that income distribution affects the dynamics of vegetation cover as much as agricultural variables. In the Agreste, a balanced interaction between climatic factors and human activities was observed, where precipitation still influences vegetation cover, but modulated by agricultural use and the presence of social programs. In the Zona da Mata, urbanization and agricultural expansion were the main modulators of vegetation cover, with emphasis on sheep and cattle farming, the presence of beneficiaries of income distribution programs, and the presence of water bodies that can act in the indirect regulation of land use. We conclude from the study carried out that the dynamics of native vegetation coverage in the analyzed mesoregions is influenced by a complex interaction of factors, presenting distinct patterns in Borborema, Agreste and Zona da Mata.